Praktik Persaingan Usaha Tidak Sehat dalam Pengadaan Barang/Jasa Pemerintah di Sektor Jasa Konstruksi - Arifin, Zaenal; Amirullah, Muhammad; Nugroho, Tri (Universitas Semarang, 2024)
The aim of this study is to study the regulation of unfair business competition in government goods/services combination (PBJ) and study the consideration of the Komisi Pengawas Persaingan Usaha (KPPU) in resolving the issue of unfair business competition construction Mandala Krida Stadium. Infrastructure development is a way of turning the wheel of society's economy. Increasing infrastructure development needs have prompted the government to create a framework for attracting private investment and participation in infrastructure projects. that the construction services sector is key in infrastructure development, which directly affects economic growth. Unfair business competition can hinder the development of quality and efficient infrastructure. The type of research used is the juridic normative. The result of this study is that the PBJ Competition Act has provided a sufficient basis for regulating and monitoring the competition of enterprises in the PBJ sector. To more ideal conditions, improvements are needed in terms of implementation and law enforcement. Strengthening inter-agency coordination, enhancing the competence of entrepreneurs, and improving supervisory capabilities, as well as the more effective use of technology can help create a healthier and fairer competitive climate in the PBJ in Indonesia. KPPU established that there has been a violation of Article 22 of the Business Competition Act. KPPU decided to grant administrative sanctions to the entrepreneurs involved, including fines and prohibition from participating in the PBJ for a certain period of time. Tujuan dari penelitian ini untuk mengkaji pengaturan persaingan usaha tidak sehat dalam pengadan barang/jasa pemerintah (PBJ) dan mengkaji pertimbangan Komisi Pengawas Persaingan Usaha (KPPU) dalam memutus perkara persaingan usaha tidak sehat pembangunan Stadion Mandala Krida. Pembangunan infrastruktur adalah cara untuk memutar roda ekonomi masyarakat. Meningkatnya kebutuhan pembangunan infrastruktur mendorong pemerintah membuat kerangka kerja untuk menarik investasi dan partisipasi swasta dalam proyek-proyek infrastruktur salah satu contoh yaitu pengadaan tender pembangunan. bahwa sektor jasa konstruksi adalah kunci dalam pembangunan infrastruktur, yang secara langsung mempengaruhi pertumbuhan ekonomi. Ketidakadilan dalam persaingan usaha dapat menghambat pembangunan infrastruktur yang berkualitas dan efisien. Jenis penelitian yang digunakan adalah yuridis normatif. Hasil dari penelitian ini adalah UU Persaingan Usaha dan Perpres PBJ telah memberikan dasar yang cukup untuk mengatur dan mengawasi persaingan usaha di sektor PBJ. Untuk mencapai kondisi yang lebih ideal, diperlukan peningkatan dalam hal implementasi dan penegakan hukum. Penguatan koordinasi antar lembaga, peningkatan kompetensi pelaku usaha, peningkatan kapabilitas pengawasan, serta pemanfaatan teknologi yang lebih efektif dapat membantu menciptakan iklim persaingan yang lebih sehat dan adil dalam PBJ di Indonesia. KPPU menetapkan bahwa telah terjadi pelanggaran Pasal 22 UU Persaingan Usaha. KPPU memutuskan untuk memberikan sanksi administratif kepada para pelaku usaha yang terlibat, termasuk denda dan larangan berpartisipasi dalam PBJ untuk jangka waktu tertentu.